Biosorption of Silver Ions by Biomass: Equilibrium, Kinetics and Thermodynamics - Hongxiang Ou; Yujun Song; Weihong Huang; Jianming Pan; Yonglai Xue; Chengwu Yi; Yongsheng Yan (Adsorption Science & Technology, 2011)
The freeze-dried biomass of Paecilomyces lilacinus was employed as a biosorbent for the removal of silver ions from aqueous solution. The effects of factors such as the solution pH, the initial Ag(I) ion concentration, contact time and temperature were examined. Maximum Ag(I) adsorption was obtained at pH 3.0. The pseudo-first-order, pseudo-second-order and intra-particle diffusion kinetic models were fitted to the experimental data when it was found that such data were best fitted by the pseudo-second-order kinetic model. The equilibrium experimental data were well fitted by the Langmuir model (R 2 > 0.995) and the maximum biosorption capacity at 298 K was 101.0 mmol/g. Thermodynamic parameters such as the Gibbs' free energy, ΔG 0 , the standard enthalpy, ΔH 0 , and the standard entropy, ΔS 0 , were evaluated. The results indicated that the biosorption of Ag(I) ions onto P. lilacinus biomass was spontaneous and endothermic in nature. The FT-IR analysis results indicated that amine, carboxylic and hydroxyl groups were involved in the biosorption process.